A court of mist and fury - Maas, Sarah J. (Court of Thorns and Roses, 2016)
Though Feyre now has the powers of the High Fae, her heart remains human, but as she navigates the feared Night Court's dark web of politics, passion, and dazzling power, a greater evil looms--and she might be key to stopping it.